Viking silver, hoards and containers - Gruszczynski, Jacek, 1980- author.
1 online resource.
Keywords: "It is widely accepted that the Viking Age (c. 800-1050) stimulated the development of long-distance, regional and local trade and exchange networks. The clearest archaeological evidence for these contacts is mainly in the form of silver artefacts, predominantly found in hoards in Northern and Central Europe - the Baltic zone. However, beyond occasional national or regional-level research, there have been no attempts at a historically guided comparative archaeological survey of the Baltic zone as a whole. By investigating silver hoards and the context of their deposition, Viking Silver, Hoards and Containers seeks to understand the variety of functions performed by hoards; the differences in function within regions; the hoards' relationship with trade; and the nature and function of emporia. It also examines the extent to which the findings mesh with literary evidence and the nature of the different societies benefiting from the influx of silver in the Viking Age. Crucially, the book features a catalogue, which provides a thorough overview and update of Baltic-zone hoards. Viking Silver, Hoards and Containers is intended for use by students of and specialists in early medieval, Viking and Slavic history and archaeology. However, it will also be a useful teaching resource for other general courses in archaeology, anthropology and material culture, numismatics, economic history, religious studies, GIS, and statistics"--